A critical systematic review of K-12 neurology/neuroscience pipeline programs - Minen, Mia T.; Lebowitz, Naomi; Ekhtman, Jane; Oza, Khushalee; Yusaf, Ishah; Katara, Aarti; Aymon, Ramisha; Plovnick, Caitlin (Frontiers in Medicine, 2023)
Background Early exposure to neuroscience is imperative to strengthening the neuroscience and neurology pipeline and may present an avenue for increasing the number of practicing neurologists and diversifying the neuroscience workforce. Our objective was to systematically review existing K-12 neuroscience education and outreach programs to understand what educational programs have been developed and implemented. Methods We conducted an electronic database search of PubMed, EMBASE, PsycINFO, Education Source, and ERIC. All eligible articles were systematically reviewed to examine the type of program developed, target age group, implementation, and efficacy. Results Our search produced 2,574 results, from which 23 articles were deemed eligible. The breakdown by age group was as follows: 5 elementary school, 8 middle school, 8 high school, and 2 general K-12 range of students. Six articles described programs intended for URM students. All programs were found to be successful in exposing students to neuroscience and inspiring interest in pursuing a career in the field of neurology. Discussion Further efforts are necessary to analyze the long-term effectiveness of K-12 neuroscience education and outreach programs in overcoming the shortage of neurologists and explore the impact of mentorship for various age groups among K-12. Systematic review registrationhttps://doi.org/10.17605/OSF.IO/2G8CN.